Perlindungan Hukum Terhadap Anak Korban Tindak Pidana Persetubuhan Secara Berlanjut - Noya, Rani; Wadjo, Hadibah Zachra; Patty, Jetty Martje (PATTIMURA Law Study Review, 2025)
Children are included in the group of rights holders. Children's rights are an inseparable part of Human Rights (HAM). These rights include the basic rights of children because they have special needs related to their position as vulnerable individuals. Cases of violence against children, including sexual violence, namely continued intercourse, still often occur. Sexual violence is a form of physical violence that is a criminal act. This type of research is normative juridical where the research is conducted by collecting primary, secondary and tertiary data obtained using literature studies. The results of this study indicate that the judge's consideration of the perpetrators of the crime of continued intercourse, namely the judge gave aggravating considerations, namely the defendant's actions disturbed the community, the defendant's actions embarrassed the victim and his family, the defendant's actions caused the victim to feel afraid and traumatized. And the mitigating factors are that the defendant regretted his actions and promised not to repeat them again, the defendant was elderly, the defendant had never been convicted, the victim's family had forgiven the defendant. Child Protection is all activities to guarantee and protect children and their rights so that they can live, grow, and develop. Special protection is a form of protection received by children in certain situations and conditions to ensure a sense of security against threats that endanger themselves and their lives during their growth and development.